The Effect Of Pedagogical Competence, Work Facilities And WorkMotivation On Teachers Performance At Sma Negeri In KelayangDistrict Indragiri Hulu Regency - Juliana Syamsunita; Kurniawaty Fitri; Mida Aprilina Tarigan (West Science Business and Management, 2025)
This study aims to analyze the effect of pedagogical competence, work facilities, and work motivation on the performance of public senior high school teachers in Kelayang District, Indragiri Hulu Regency. The study employs a quantitative approach with a population consisting of public senior high school teachers in Kelayang District, Indragiri Hulu Regency. The sample was selected using purposive sampling, resulting in 37 teachers with civil servant (PNS) status being chosen as respondents out of a total population of 55 teachers. Data analysis in this study was conducted using descriptive statistical analysis, data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Data processing was assisted by SPSS version 22 software. The results of the study indicate that pedagogical competence, work facilities, and work motivation have a positive and significant effect on teacher performance, both partially and simultaneously. Based on the coefficient of determination (R²), the three independent variables collectively contribute 57.9% to the dependent variable, while the remaining 42.1% is influenced by other variables not included in this study.